Revolution within the Revolution : Women and Gender Politics in Cuba, 1952-1962 - Chase, Michelle (Book collections on Project MUSE., 2015)
"A handful of celebrated photographs show armed, fatigues-clad female Cuban insurgents alongside their compañeros in Cuba's remote mountains during the revolutionary struggle. However, the story of women's part in the struggle's success only now receives comprehensive consideration in Michelle Chase's history of women and gender politics in revolutionary Cuba. Restoring to history women's participation in the all-important urban insurrection, and resisting Fidel Castro's triumphant claim that women's emancipation was handed to them as a 'revolution within the revolution, ' Chase's work demonstrates that women's activism and leadership was critical at every stage of the revolutionary process."--